Landscape in cultural tourism: the example of an Olęder settlement in Wielkopolska - Przewoźny, Witold (Turystyka i krajoznawstwo, 2021)
The rural cultural landscape is more and more often a target of tourist interest. Not only are material heritage monuments discovered, but other aspects, until recently unknown, as well. These include traces of a former settlement under Olęder law. Vast meadows, canals overgrown with willows and poplars, or lonely farms are often the only traces of the Olęder presence. Together with the rural architecture with its Mennonite- Dutch history, they are the tourist attraction which Żuławy is famous for. Olęder villages in the region of Toruń, Bydgoszcz, Warsaw and Sławatycze are also visited. In Wielkopolska efforts have been made to promote the post-Olęder cultural landscape (over 900 villages) and the vicinity of Nekla and the lonely settlements of the Pyzdry Forest play a special role here. Until recently, the rural parts of these areas were considered unattractive (with the exception of the backwaters of the Nadwarciański Landscape Park) but the discovery of „Olęder history” has given these areas a new, and extremely interesting, meaning.